Pemanfaatan Media Youtube dalam meningkatkan Pemahaman Program KB di KP KB Insan Sejahtera Desa Sukajaya Lembang - Dilla Indriasari (IKIP Siliwangi, 2020)
This study examines the role of the youtube media and understanding of the family planning program, the research problem is how the role of the youtube media in enhancing the understanding of the family planning program. Family Planning is an effort to plan also to control the population through the use of contraceptive methods in an effort to create economic and social benefits for all levels of the population. By increasing community participation in the use of KB MKJP. KB counseling is expected to help fertile age cuouples in choosing the right contraception. The use of Non MKJP is very dominating, meaning that many people still do not understand the importance of KB MKJP. Because family planning counseling has not been reached at all levels of society because of the limited extension workers. YouTube media can provide family planning information and help people choose the right contraceptive method for themselves. This study aims to find out the description of the family planning program and how the use of YouTube media in enhancing the understanding of family planning in the Insan Sejahtera family planning family planning company. In this study, researchers used a descriptive method with a qualitative approach. Data collected through interviews, observation and documentation. The population of the study was 327 fertile age cuouples with a sample of 10 fertile age cuouples using Non MKJP. The results showed that youtube media was effective in increasing understanding of the family planning program, as seen from the difference between before and after the introduction of the youtube media. Understanding of the family planning program is demonstrated by community participation in the use of the MKJP.